STUDENTS’ PERCEPTION ON THE UTILIZATION OF ZOOM VIDEO CONFERENCING IN IMPROVING SPEAKING ABILITY AMIDST COVID-19 PANDEMIC - Dinda Rachmitha Noviyanti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2022)
This research investigated about students’ perception on the utilization of Zoom Video Conferencing in improving speaking ability in the midst of COVID-19 outbreak. These days, the conventional class were converted into distance learning to prevent the contagious outbreak COVID-19. Therefore, this situation influenced the teachers and students to utilize Zoom Video Conferencing as their learning media. Thus, this research applied Mix Methods Approach by using closed-ended questionnaire and open-ended questionnaire which is adopted and modified from Bawanti’s study (2021). These questionnaires were distributed by Google Form through WhatsApp and Twitter to 103 junior high school and high school student in Jabodetabek area. As the result, it discovered that Zoom Video Conferencing can help the students to develop positive attitude and have a great impact for developing speaking skills. Students feel they never feel afraid to volunteer themselves to speaking English in the classroom. Zoom also facilitates students and teachers to have direct communication, discussion, and teaching and learning process with its features as face-to-face classroom owns.